PENGEMBANGAN MEDIA LAPANGAN KARTESIUS BERBASIS PERMAINAN GOBAK SODOR PADA MATERI TITIK KOORDINAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SDN 107400 BANDAR KHALIPAH - Halimatus Azizah Hutasuhut; Elvi Mailani; Zainuddin Muchtar; Syahrial; Natalia Silalahi (STKIP Subang, 2026)
This study aims to determine the validity, practicality, and effectiveness of the Cartesian Plane learning media based on the Gobak Sodor game on the coordinate point material for sixth grade students of SDN 107400 Bandar Khalipah. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The validation results show an average percentage of 89%, categorized as very feasible. The practicality aspect obtained a score of 92%, which indicates that the media is easy to use by teachers and students and supports conducive learning. This media presents concrete and interactive visualizations of the concept of coordinate points through game activities, helping students understand the position of points on the Cartesian plane more meaningfully. The effectiveness test was carried out through pre-tests and post-tests, with the average score increasing from 38.25% to 81.85%. The N-Gain calculation result of 0.6643 is included in the fairly high category. Based on these results, the learning media is declared valid, practical, and effective in improving student learning outcomes. Thus, this media has the potential to be applied more widely and developed in other educational materials and levels.